COMPARISON OF EFFICACY OF ORAL FLUCONAZOLE WITH INTRAMUSCULAR MEGLUMINE ANTIMONIATE IN TREATMENT OF CUTANEOUS LEISHMANIASIS: Treatment of Cutaneous Leishmaniasis - Mazhar, Hina; Hassan, Faiz -ul-; Dilnawaz, Mansoor (Pakistan Armed Forces Medical Journal, 2015)
Objective:  To compare the efficacy of oral fluconazole with intramuscular meglumine antimoniate in patients of cutaneous leishmaniasis.Study Design:  Randomized Control Trial.Place and Duration of Study: Study was conducted from 1st January 2013 to 30th June 2013, at Dermatology department, Military Hospital, Rawalpindi.Patients and Methods: Eighty histopathologically diagnosed patients of cutaneous leishmaniasis were selected. Patients were randomly allocated into two groups. Group-A was given oral fluconazole 200mg/day for six weeks. Group-B was given intramuscular meglumine antimoniate 20 mg/kg/day for 21 days. Status of each lesion was regularly documented and efficacy of drugs was measured at the end of three months. The drug was considered efficacious if there is more than 75% regression in size and induration of lesions.Results: Clinical efficacy was seen in 70% (n=28) in Group-A and 92.7% (n=37) in Group-B at end of three months. When compared by Chi-square test, these results were found to be statistically significant with p-value 0.010(< 0.05)Conclusion: Efficacy of Intramuscular meglumine antimoniate is better than oral fluconazole in treatment of cutaneous leishmaniasis.